Age-Characteristic Changes of Glucose Metabolism, Pancreatic Morphology and Function in Male Offspring Rats Induced by Prenatal Ethanol Exposure - Xiao, Di; Kou, Hao; Gui, Shuxia; Ji, Zhenyu; Guo, Yu; Wu, Yin; Wang, Hui (Frontiers in Endocrinology, 2019)
Intrauterine growth restricted offspring suffer from abnormal glucose homeostasis and β cell dysfunction. In this study, we observed the dynamic changes of glucose metabolic phenotype, pancreatic morphology and insulin synthesis in prenatal ethanol exposure (PEE) male offspring rats, and to explore the potential intrauterine programming mechanism of the glucocorticoid-insulin-like growth factor 1 (GC-IGF1) axis. Ethanol (4 g/kg·d) was administered through oral gavage during gestational day (GD) 9-20. Serum glucose and insulin levels, pancreatic β cell mass, and expression of glucocorticoid receptor (GR), IGF1 and insulin were determined on GD20, postnatal week (PW) 6, PW12 with/without chronic stress (CS), and PW24, respectively. Both intraperitoneal glucose and insulin tolerance tests were conducted at PW12 and PW24. Results showed that the serum glucose and insulin levels as well as pancreatic β cell mass were reduced on GD20 in PEE males compared with the controls, while pancreatic GR expression was enhanced but IGF1 and INS1/2 expression were suppressed. After birth, compared with the controls, β cell mass in the PEE males was initially decreased at PW6 and gradually recovered from PW12 to PW24, which was accompanied by increased serum glucose/insulin levels and insulin resistance index (IRI) at PW6 and decreased serum glucose contents at PW12, as well as unchanged serum glucose/insulin concentrations at PW24. In addition, both improved glucose tolerance and impaired insulin sensitivity of the PEE males at PW12 were inversed at PW24. Moreover, at PW6 and PW12, pancreatic GR expression in the PEE group was decreased, while IGF1 expression was reversely increased, resulting in a compensatory increase of insulin expression. Moreover, CS induced pancreatic GR activation and inhibited IGF1 expression, resulting in impaired insulin biosynthesis. Conclusively, the above changes were associated with age and the intrauterine programming alteration of GC-IGF1 axis may be involved in prenatal and postnatal pancreatic dysplasia and impaired insulin biosynthesis in PEE male offspring.